Identification of a novel interaction site between the large hepatitis delta antigen and clathrin that regulates the assembly of genotype III hepatitis delta virus - Wei-Chung Chiou; Hsu-Feng Lu; Jui-Chieh Chen; Yu-Heng Lai; Ming-Fu Chang; Yuan-Li Huang; Ni Tien; Cheng Huang (figshare, 2022)
Abstract Background Hepatitis delta virus (HDV), a satellite virus of hepatitis B virus (HBV), is a small, defective RNA virus strongly associated with the most severe form of hepatitis and progressive chronic liver disease and cirrhosis. Chronic hepatitis D, resulting from HBV/HDV coinfection, is considered to be the most severe form of viral hepatitis and affects 12–20 million people worldwide. Involved in the endocytosis and exocytosis of cellular and viral proteins, clathrin contributes to the pathogenesis and morphogenesis of HDV. Previously, we demonstrated that HDV-I and -II large hepatitis delta antigens (HDAg-L) possess a putative clathrin box that interacts with clathrin heavy chain (CHC) and supports HDV assembly. Methods Virus assembly and vesicular trafficking of HDV virus-like particles (VLPs) were evaluated in Huh7 cells expressing HDV-I, -II and -III HDAg-L and hepatitis B surface antigen (HBsAg). To elucidate the interaction motif between HDAg-L and CHC, site-directed mutagenesis was performed to introduce mutations into HDAg-L and CHC and analyzed using coimmunoprecipitation or pull-down assays. Results Comparable to HDV-I virus-like particles (VLPs), HDV-III VLPs were produced at a similar level and secreted into the medium via clathrin-mediated post-Golgi vesicular trafficking. Mutation at F27 or E33 of CHC abolished the binding of CHC to the C-terminus of HDV-III HDAg-L. Mutation at W207 of HDV-III HDAg-L inhibited its association with CHC and interfered with HDV-III VLP formation. We elucidated mechanism of the binding of HDV-III HDAg-L to CHC and confirmed the pivotal role of clathrin binding in the assembly of genotype III HDV. Conclusions A novel W box which was identified at the C terminus of HDV-III HDAg-L is known to differ from the conventional clathrin box but also interacts with CHC. The novel W box of HDAg-L constitutes a new molecular target for anti-HDV-III therapeutics.
Keywords: Biophysics; Biochemistry; Cell Biology; Molecular Biology; Environmental Sciences not elsewhere classified; Chemical Sciences not elsewhere classified; Ecology; Mental Health; Infectious Diseases; Virology